SEBUAH WACANA HAM TENTANG “HAK ATAS KEPEMILIKAN” - Nalom Kurniawan (Universitas Widya Gama Malang, 2019)
Among vatious rights in the human rights discourse. The right of ownership is one of the rightswhich is interesting to discuss. It is because regulations of rights of ownership is not stated inthe derivation of the UDHCR (ICCPR/ICESCR) covenant. Moreover, various concepts andviews on the rights of ownership have different characteristics and uniqueness. Protection ofthe right of ownership may conflict with other rights (public interest).